Photoelectrocatalytic reduction of CO2 to syngas over Ag nanoparticle modified p-Si nanowire arrays. Issue 26 (10th June 2019) - Wei, Longfu; Lin, Jinchi; Xie, Shunji; Ma, Wenchao; Zhang, Qinghong; Shen, Zebin; Wang, Ye
Abstract : Syngas with tunable H2 /CO distribution is produced from the photoelectrocatalytic reduction of CO2 and H2 O over Ag/SiNWs by controlling Ag sizes. Abstract : The solar energy-driven reduction of CO2 and H2 O to syngas (H2 /CO), an important platform to produce chemicals, is of significance for alleviating greenhouse gas emission and utilizing sustainable solar energy. Here, we report a facile method for the photoelectrocatalytic reduction of CO2 and H2 O to syngas over an Ag nanoparticle (NP) modified p-Si nanowire array catalyst. The particle size of Ag significantly influences the activity of CO2 reduction to CO. The H2 /CO molar ratio in reduction products can be tuned in the range from 1 to 4 by controlling the size of Ag NPs from 4.2 to 16 nm. The adsorption strength of CO on the catalyst was found to decline with the increase in the size of Ag NPs. The Ag NPs of 8.2 nm, which possess a moderate CO adsorption strength, exhibit the maximum production of CO with the H2 /CO ratio of 2/1.